Induction Chemotherapy Followed by Concurrent Full-dose Gemcitabine and Intensity-modulated Radiation Therapy for Borderline Resectable and Locally Advanced Pancreatic Adenocarcinoma. (February 2016) - Badiyan, Shahed N.; Olsen, Jeffrey R.; Lee, Andrew Y.; Yano, Motoyo; Menias, Christine O.; Khwaja, Shariq; Wang-Gillam, Andrea; Strasberg, Steven M.; Hawkins, William G.; Linehan, David C.; Myerson, Robert J.; Parikh, Parag J.
Abstract : Objective: To evaluate the outcomes and toxicity of concurrent full-dose gemcitabine and intensity-modulated radiation therapy (IMRT) for patients with borderline resectable and locally advanced pancreatic adenocarcinoma after induction chemotherapy. Materials and Methods: From 2009 to 2012, 32 patients were treated with concurrent gemcitabine and IMRT for borderline resectable or locally advanced pancreatic adenocarcinoma. All patients received induction FOLFIRINOX or gemcitabine-based chemotherapy before chemoradiation. The radiotherapy volume was limited to the primary tumor, and the median dose was 55 Gy in 25 fractions. Gemcitabine was administered weekly during radiotherapy on days 1, 8, 22, and 29 at a median weekly dose of 800 mg/m 2 . Results: Twenty-five patients had locally advanced disease and 7 had borderline resectable disease. The median follow-up time was 14.6 months. The median progression-free and overall survival were 13.9 and 23.1 months, with a trend toward improved overall survival for patients receiving induction FOLFIRINOX compared with gemcitabine-based therapy. A radiographic complete or partial response was achieved in 13 patients (41%), with 4 (13%) having complete radiographic responses. Surgical resection was performed in 10 patients (31%)—6 patients with locally advanced disease and 4 with borderline resectable disease. Grade 3/4 hematologic toxicity during and up to 6 weeks after chemoradiation occurred in 12 patients (38%); grade 3 nonhematologic toxicity occurred in 7 patients (22%), with no grade 4 or 5 toxicity. All patients completed their radiotherapy. Conclusions: Concurrent full-dose gemcitabine and limited-field IMRT after induction chemotherapy for the treatment of borderline resectable and locally advanced pancreatic cancer is promising with acceptable toxicity rates.